Efek Ekstrak Metanol Daun Jamblang (Syzygium cumini) Pada Keong Mas (Pomacea canaliculata): Effects of Jamblang Leaves Methanol Extract (Syzygium cumini) on Mas Snail (Pomacea canaliculata) - Amanda Firmansyah; Firdaus; Hamzah (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
The mas snail (Pomacea canaliculata) is one of the pests of paddy’s plant that needs to be controlled because it can attack the nursery and paddy that is ready to be harvested. Jamblang leaves are known to have biactive secondary metabolites such as alkaloids, flavanoids, saponins, terpenoids and tannins. The purpose of this study was to test the methanol extract of jamblang leaves on the mas snail. This research was conducted by extracting 1000ml of jamblang leaf powder with 1000ml of methanol for 3 days, then the extraction results were thickened and made into several doses of 0 ml/L (P0), 1 ml/L (P1), 2 ml/L (P2), 3 ml/L (P3). ). 4ml/L (P4) and 5ml/L (P5). Each dose was tested on 10 golden snails that had been given well water and gamal leaves as feed. The results showed that the 5ml/L (P5) treatment caused 100% mortality at 48JSA and the lowest attack intensity on gamal feed was 8.33%.